2017
DOI: 10.1186/s12868-016-0325-0
|View full text |Cite
|
Sign up to set email alerts
|

CX3C chemokine receptor 1 deficiency modulates microglia morphology but does not affect lesion size and short-term deficits after experimental stroke

Abstract: BackgroundThe fractalkine/CX3C chemokine receptor 1 (CX3CR1) pathway has been identified to play an essential role in the chemotaxis of microglia, leukocyte trafficking and microglia/macrophage recruitment. It has also been shown to be important in the regulation of the inflammatory response in the early phase after experimental stroke. The present study was performed to investigate if CX3CR1 deficiency affects microglia during the first 14 days with consequences for tissue damage after experimental stroke.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Regarding CX3CR1, its deficiency provides a neuroprotective effect against ischemia-induced brain injury in mice following focal cerebral ischemia (18,22,37). However, a recent study has shown that CX3CR1 deficiency does not affect lesion size after transient focal cerebral ischemia in mice (38).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CX3CR1, its deficiency provides a neuroprotective effect against ischemia-induced brain injury in mice following focal cerebral ischemia (18,22,37). However, a recent study has shown that CX3CR1 deficiency does not affect lesion size after transient focal cerebral ischemia in mice (38).…”
Section: Discussionmentioning
confidence: 99%
“…stroke (60,61). Although the CC3CL1/CX3CR1 pathway has been shown to contribute to ischemic injury in mice (62)(63)(64), whether this is due to changes in neuronal-microglial interactions remains to be established.…”
Section: Complementmentioning
confidence: 99%
“…24 h might be due to effects on multiple processes i.e. brain edema without consequences for the final ischemic lesion and function [ 44 ]. Also, differences in results might be due to different experimental stroke models.…”
Section: Discussionmentioning
confidence: 99%